Didžiojo tėvynės karo metais į šalies gilumą pasitraukusių Lietuvos piliečių bibliotekinis aptarnavimas - Sinkevičius, Klemensas (Knygotyra, 1985)
When the Hitlerite soldiery began to occupy parts of the Soviet territory, in the first place Lithuania, 22,671 Lithuanian citizens evacuated to the depth of the Soviet union.The library system of the country was adapted to work under war conditions. Much attention was paid to the evacuees service.In 1942 the Moscow editing houses began to publish books in the Lithuanian language. Thus started the acquisition of Lithuanian literature for the Lithuanian children’s homes and schools and for the libraries of the courses at the Central Committee of the Lithuanian Communist Party and for Soviet and Party active members.The libraries helped the evacuees to work and to learn, to contribute to the common fight of the Soviet people against fascism.